Minilaparoscopic Versus Conventional Laparoscopic Hysterectomy: Insights from a Single-Center Retrospective Cohort Study with Legal Considerations - Valentina Billone; Giuseppe Gullo; Eleonora Conti; Silvia Ganduscio; Sofia Burgio; Giovanni Baglio; Gaspare Cucinella; Lina De Paola; Susanna Marinelli (Medicina)
Background and Objectives: We compared mini-laparoscopic and laparoscopic hysterectomy in terms of surgery duration, postoperative pain, conversion rate, blood loss, postoperative complications (Clavien-Dindo classification), and the length of hospital stay. Materials and Methods: Patients were recruited between 1 January 2017 and 1 January 2024, at the Department of Gynecology, “Villa Sofia-Cervello” Hospital. Indications for hysterectomy included uterine myoma, endometriosis, endometrial hyperplasia, adenomyosis, high-grade cervical dysplasia, early-stage endometrial cancer, and microinvasive cervical cancer. Patients were divided according to treatment into conventional laparoscopic hysterectomy (LH) with all 5 mm ports or the needlescopic approach (minilaparoscopic hysterectomy [MLH]), using 3 mm instruments. Postoperative pain was assessed using the visual analog scale (VAS) at multiple time points (2, 6, 12, and 24 h post-surgery). Results: A total of 308 patients were enrolled, with 153 women in the LH group and 155 in the MLH group. The surgery duration was on average 105.5 min in LH and 98.8 min in MLH (p < 0.0001). The intraoperative blood loss averaged 195.1 mL in LH and 100.3 mL in MLH (p < 0.001). The average length of hospital stay was 4.0 days for women undergoing LH compared to 3.2 days for women undergoing MLH (p < 0.001). Conclusions: This retrospective study demonstrated that MLH is an effective and functional technique for treating various gynecological conditions, with advantages in terms of aesthetic outcomes and reduced perioperative pain and recovery times. The positive results, supported by key parameters such as surgical duration, blood loss, and complications, could serve as a foundation for future studies on larger populations and for improving clinical practices in gynecology.